ANALISIS KEMAMPUAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PKN SDN X BATUSANGKAR - Anggina Yulita; Safrizal; Sunarti (Jurnal Pendidikan Dasar dan Keguruan, 2023)
In an effort to boost the learning motivation of high school elementary school students, the teacher's efforts to leave this learning open at the end of the PKN semester. Understanding and improving student learning outcomes in PKN learning can be supplemented by increasing learning motivation. The aim of this study was to identify teacher tools to increase the learning motivation of high school elementary students during PKN classes. This study uses a qualitative case study methodology. The method used to gather information for this study is called objective sampling. In this research instrument, the researchers themselves collected data using observation techniques, questionnaires, and document analysis. Data analysis techniques use data collection, editorial, display, and conclusion steps. The guarantor of the validity of the data in this third study combines the method of collecting data by combining triangulation. The results of the study indicated the need for greater motivation to teach high grade students during Internship classes. One of the factors that causes students' learning motivation to be lower than it should be is their exposure to less than ideal learning environments and less than ideal teaching methods. Therefore the advice given by the teacher to increase student learning motivation is to use teaching strategies that can do this. This includes offering counselling services and using ice-breaker activities such as games and ice hockey.